2020
DOI: 10.3389/fpsyt.2019.00979
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Presentations to Child and Adolescent Psychiatry: Nonsuicidal Self-Injury and Suicidality

Abstract: Nonsuicidal Self-Injury (NSSI) and suicidality are common reasons for emergency presentations in child and adolescent psychiatry. Therefore, we focused on reasons for emergency presentations as well as specific characteristics of those presenting with NSSI or suicidality to an emergeny psychiatric service. We analyzed data from a German university hospital regarding emergency presentations during a 78 months' period. NSSI and suicidality were rated according to the Columbia Classification Algorithm of Suicide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
3
14
0
2
Order By: Relevance
“…The above-mentioned study ( 5 ) deals with patients under 18 years who visited the emergency pediatric department who needed psychiatric evaluation, while in our case a distinct selection was made of NSSI and suicidal behavior in a child and adolescent psychiatric setting. The higher proportion of girls has also been confirmed in other studies on NSSI and suicide attempts in adolescents ( 20 , 59 , 60 ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The above-mentioned study ( 5 ) deals with patients under 18 years who visited the emergency pediatric department who needed psychiatric evaluation, while in our case a distinct selection was made of NSSI and suicidal behavior in a child and adolescent psychiatric setting. The higher proportion of girls has also been confirmed in other studies on NSSI and suicide attempts in adolescents ( 20 , 59 , 60 ).…”
Section: Discussionsupporting
confidence: 78%
“…psychiatric setting. The higher proportion of girls has also been confirmed in other studies on NSSI and suicide attempts in adolescents (20,59,60). We also interviewed the custodians of our adolescent patients about the psychiatric history of family members.…”
Section: Discussionsupporting
confidence: 70%
“…Primary indication for psychiatric consultation was suicidal ideation at 39% in another survey from a pediatric emergency department in the USA (35). NSSI led to 36.6% of emergency presentations in a retrospective chart review of a clinic for child and adolescent psychiatry in Germany (33). Suicidal ideation was the most common reason for emergency presentation in our study, accounting for 54.2%.…”
Section: Discussionmentioning
confidence: 53%
“…Overall, 57.8% of the emergency presentations in our clinic were female and the average age of presentations was 15;4 years. With regard to the sex distribution and mean age during the emergency consultation a previous study in Germany (33) revealed approximately similar findings (14.5 years, 56.2% females), whereas a recent study in France (13) which captured a longer time period starting from 1981 found a younger age (13;10 years) and a slightly higher rate of male children and adolescents (aggressive behavior as a frequent reason for presentation is likely to explain the higher proportion of boys).…”
Section: Discussionmentioning
confidence: 99%
“…These factors can thus make them more vulnerable to behaviors that intentionally cause harm to their health, such as self-destructive behaviors, 3 which have been responsible for most of the care provided to children and adolescents in emergency services. 4 Non-suicidal self-injury (NSSI) is an action with no conscious intention of suicide, but which can generate serious injuries. This behavior is related to mechanisms of coping with emotions, it is often used to decrease tension or relieve suffering and, generally, it is related to negative interpersonal relationships.…”
Section: Introductionmentioning
confidence: 99%